2020
DOI: 10.3390/app10196957
|View full text |Cite
|
Sign up to set email alerts
|

Reliability-Based Preventive Maintenance Strategy of Truck Unloading Systems

Abstract: The unloading of petroleum products is a complex and potentially dangerous operation since the unloading system contains complex interdependency components. Any failures in one of its components lead to a cut in the petroleum supply chain. Therefore, it is important to assess and evaluate the reliability of the unloading system in order to improve its availability. In this context, this paper presents the operation philosophy of the truck unloading system, failure modes of the components within the system, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…For example, as mentioned in [5], the supply chain of petroleum products faces major challenges, i.e., demand growth and the complexity of fluid transportation. The petroleum supply chain contains multiple stations extending from oil wells in exploration and production areas to the final destination.…”
Section: Innovations In Maintenance Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, as mentioned in [5], the supply chain of petroleum products faces major challenges, i.e., demand growth and the complexity of fluid transportation. The petroleum supply chain contains multiple stations extending from oil wells in exploration and production areas to the final destination.…”
Section: Innovations In Maintenance Strategiesmentioning
confidence: 99%
“…Therefore, it is important to assess and evaluate the reliability of the unloading system in order to improve its availability. In this context, Mohammed et al [5] present the operation philosophy of the truck unloading system, failure modes of the components within the system, and a bottom-up approach to analyze the reliability of the system. In addition, it provides reliabil-ity data, such as failure rates and the mean time between failures of the system components.…”
Section: Innovations In Maintenance Strategiesmentioning
confidence: 99%
“…Preventive maintenance (PM) is a calendar-based program in which very comprehensive test routines are applied to off-line equipment [10]. In a PM program, data are collected during both on-line and off-line periods.…”
Section: Planned Maintenancementioning
confidence: 99%
“…As it is explained earlier, the motivation of the paper is due the importance of finding the number of failures in the field of maintenance strategy. Some examples of such importance can be seen in [11][12][13][14][15][16] from various perspectives. It is often found that most of the problems in maintenance engineering are finding optimal strategies that minimize the cost of operation to manipulate the system as well as minimize the number of failures of the system (e.g., [17]).…”
Section: Literature Reviewmentioning
confidence: 99%